Effectiveness of an Attachment-Based Intervention Program in Promoting Emotion Regulation and Attachment in Adolescent Mothers and their Infants: A Pilot Study - Riva Crugnola, Cristina; Ierardi, Elena; Albizzati, Alessandro; Downing, George (Frontiers in Psychology, 2016)
This pilot study examined the effectiveness of an attachment-based intervention program, PRERAYMI, based on video technique, psychological counseling and developmental guidance in improving the style of interaction and emotion regulation of adolescent mothers and their infants after 3 and 6 months of intervention. Analyses revealed that adolescent mothers who participated in the intervention (vs. control group adolescent mothers) increased their Sensitivity and reduced their Controlling style after both 3 and 6 months of treatment. Infants who participated in the intervention (vs. control group infants) increased their Cooperative style and reduced their Passive style from 3 to 9 months. Moreover, the intervention group dyads (vs. control group dyads) increased the amount of time spent in affective positive coordination states (matches), decreased the amount of time spent in affective mismatches, and had a greater ability to repair mismatches from 3 to 9 months. Furthermore, the intervention group dyads (vs. control group dyads) increased the amount of time spent in reciprocal involvement in play with objects from 3 to 9 months. The quality of maternal attachment did not affect the intervention effect.